The dynamics of tree species population in a Montane Araucaria forest fragment in Lages, Santa Catarina state Dinâmica de populações de espécies arbóreas em um fragmento de floresta Ombrófila mista Montana em Lages, Santa Catarina - Salami B.* (2017)
© 2017, Universidade Federal de Santa Maria. All rights reserved.The present study aimed to evaluate the tree species population dynamics in a fragment of Montane Araucaria Forest, in the municipality of Lages, Santa Catarina (SC) state, along a period of four years (2008-2012). For this, for all species sampled, in 50 permanent plots of 10x20m, the regeneration guilds [pioneer (P), light-demanding climax (LDC) and shade-tolerant climax (STC)] and dynamics rates were determined (mortality, recruitment, loss and gain in basal area, net change in abundance and basal area). The existence of significant association between regeneration guilds and dynamic rates was verified by chi- square tests, applied to contingency tables. Changes in relative participation of regeneration guilds between years were analyzed using proportion tests. In 2008, 87 species were found (P: 9, LDC: 64, STC: 11, non- classified: 3), 1.841 ind.ha-1 and 36.17 m².ha-1. In 2012, 86 species (P: 9, LDC: 63, STC: 11, non-classified: 3), 1.882 ind.ha-1 and 39.17 m².ha-1 were observed. Most species showed gains in basal area. Among the most abundant, the highest rates of recruitment and basal area gain were observed for Banara tomentosa Clos, with, respectively, 5.43%.year-1 and 6.08%.year-1, and the highest rates of mortality and basal area loss occurred for Zanthoxylum rhoifolium Lam., with, respectively, 7.75%.year-1 and 4.74%.year-1. No significant association between the dynamics patterns and regeneration guilds was observed, whose relative participations in the community, during the evaluated period, were constants. Therefore, it is possible to conclude that the forest fragment is in the process of structural instability, indicated by the increment of the number of individuals and basal area, and floristic-successional stability, due to the low floristic substitution and maintenance of the relative importance of the regeneration guilds, along the evaluated period.